Same Performance Changes after Live High-Train Low in Normobaric vs. Hypobaric Hypoxia - Saugy, Jonas J.; Schmitt, Laurent; Hauser, Anna; Constantin, Guillaume; Cejuela, Roberto; Faiss, Raphael; Wehrlin, Jon P.; Rosset, Jérémie; Robinson, Neil; Millet, Grégoire P. (Frontiers in Physiology, 2016)
Purpose: We investigated the changes in physiological and performance parameters after a Live High-Train Low (LHTL) altitude camp in normobaric (NH) or hypobaric hypoxia (HH) to reproduce the actual training practices of endurance athletes using a crossover-designed study. Methods: Well-trained triathletes (n=16) were split into two groups and completed two 18-day LTHL camps during which they trained at 1100-1200 m and lived at 2250 m (PiO2 = 111.9 ± 0.6 vs. 111.6 ± 0.6 mmHg) under NH (hypoxic chamber; FiO2 18.05 ± 0.03%) or HH (real altitude; barometric pressure 580.2 ± 2.9 mmHg) conditions. The subjects completed the NH and HH camps with a one-year washout period. Measurements and protocol were identical for both phases of the crossover study. Oxygen saturation (SpO2) was constantly recorded nightly. PiO2 and training loads were matched daily. Blood samples and VO2max were measured before (Pre-) and 1 day after (Post-1) LHTL. A 3-km running-test was performed near sea level before and 1, 7, and 21 days after training camps. Results: Total hypoxic exposure was lower for NH than for HH during LHTL (230 vs. 310 h; P<0.001). Nocturnal SpO2 was higher in NH than in HH (92.4 ± 1.2 vs. 91.3 ± 1.0%, P<0.001). VO2max increased to the same extent for NH and HH (4.9 ± 5.6 vs. 3.2 ± 5.1%). No difference was found in hematological parameters. The 3-km run time was significantly faster in both conditions 21 days after LHTL (4.5 ± 5.0 vs. 6.2 ± 6.4% for NH and HH), and no difference between conditions was found at any time. Conclusion: Increases in VO2max and performance enhancement were similar between NH and HH conditions.